Tonkawa texts a new linguistic edition - Hoijer, Harry 1904-1976; Wier, Thomas R. 1979-; Wier, Thomas R. 1979- (University of Oklahoma Press, 2018)
"This book represents the entire remaining oral literature of the Tonkawa people, edited and presented in the original Tonkawa and translated into English along with a wholly new and up-to-date grammatical description. It consists of two different kinds of stories: Night Stories, set in the pre-human mythological past, and Old Stories, in which humans get caught up in unexpected adventures."...Provided by publisher
Includes bibliographical references (pages 293-294) and index
Keywords: Tonkawa Indians -- Folklore; Tonkawa language -- Grammar; Tonkawa language -- Texts; Erzählung; Englisch; Tonkawa-Sprache; Grammatik; Übersetzung